Peran afirmasi positif dalam menumbuhkan resiliensi dan penerimaan citra diri positif pada pasien pasca-amputasi: - - Idawati Manurung; Oki Alfaro; Tori Rihiantoro; Yuliati Amperaningsih (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Amputation is an event that triggers maladaptive grief responses and impaired self-image perception due to the permanent loss of a body part. Purpose: To analyze the effect of a positive affirmation intervention on maladaptive grief responses and self-image perception in post-amputation patients. Method: Quasi-experimental, one-group pretest-posttest. A sample of 30 post-amputation patients was selected using a purposive sampling technique. The positive affirmation intervention was administered over eight sessions. Data were analyzed for grief response variables (Wilcoxon test) and self-image variables (paired sample t-test). The instruments used were a grief response questionnaire and a self-image questionnaire. Results: The majority of respondents, productive adults (20-44 years old), had a significantly decreased mean maladaptive grief score from 47.93 to 26.1 (p < 0.05); and negative self-image perception scores decreased significantly from 77.93 to 41.30 (p < 0.05). Changes in self-image were slower than the grief adaptation process. Comparison of Effect Size values ​​indicates that the grief process (12.25) and self-image perception (5.49) both fall into the Very Large Effect category, and the positive affirmation intervention had the strongest influence on changes in grief responses. Conclusion: The positive affirmation intervention was effective in eliciting and enhancing adaptive grief responses and positive self-image perceptions. Keywords: Amputation; Body Image; Grieving; Positive Affirmation. Pendahuluan: Amputasi merupakan peristiwa yang memicu respons berduka maladaptif dan gangguan persepsi citra diri akibat hilangnya bagian tubuh secara permanen. Tujuan: Untuk menganalisis pengaruh intervensi afirmasi positif terhadap respons berduka maladaptif dan persepsi citra diri pada pasien pasca-amputasi. Metode: Quasi-experiment, one-group pretest-posttest. Sampel sebanyak 30 pasien pasca-amputasi, dengan teknik purposive sampling. Intervensi afirmasi positif diberikan selama 8 sesi. Analisis data untuk variabel respons berduka (uji Wilcoxon) dan variabel citra diri (uji paired sample t-test). Instrumen adalah kuesioner respons berduka dan kuesioner citra diri. Hasil: Mayoritas responden, usia dewasa produktif (20-44 tahun), rata-rata skor berduka maladaptif menurun secara signifikan dari 47.93 menjadi 26.1 (p < 0.05); skor persepsi citra diri negatif menurun secara signifikan dari 77.93 menjadi 41.30 (p < 0.05). Perubahan pada citra diri lebih lambat dibandingkan dengan proses adaptasi berduka. Perbandingan nilai Effect Size menunjukkan proses berduka (12.25), dan persepsi citra diri (5.49), keduanya termasuk kategori Very Large Effect, dan intervensi afirmasi positif paling kuat memengaruhi perubahan respons berduka. Simpulan: Intervensi afirmasi positif efektif membangkitkan dan meningkatkan respons berduka yang adaptif serta persepsi citra diri yang positif. Kata Kunci: Afirmasi Positif; Amputasi; Berduka; Citra Diri.